La Zona Franca Permanente Modelo de Desarrollo Estratégico y Empresarial en la Ciudad de Santa Marta - Villar López, Alcides Enrique (Universidad Antonio Nariño, 2022)
Because the free trade zones have been taking great relevance for the economic development of the country and especially has been a tool for trade used by those businesses seeking to increase their profits, but the free trade zones are also good options for those organizations engaged in production and are even used by the health sector that makes the sectors more competitive nationally and internationally, by means of this monograph we seek to analyze the permanent free trade zones (ZFP) (ZFP Tayrona, ZFP Las Americas, ZFP Santa Marta) of the city of Santa Marta analyzing the operational form and the trade statistics of the last two years 2020-2021 of these free trade zones according to the historical information provided by official sources such as DANE this method is descriptive analytical type, reaching a conclusion of what is their contribution to the total of permanent free trade zones of the country and to the development of the city of Santa Marta